Salivary Electrolytes, Total Protein and Immunoglobulin A in Patients with Chronic Kidney Disease: A Case Control Study (Nigerian Journal of Physiological Sciences, 2021)
Summary: The objectives of this study were to compare levels salivary electrolytes, total protein and immunoglobulin A (IgA) in patients with chronic kidney disease (CKD) and healthy individuals; and to determine the relationship between the salivary and blood levels of these factors between the two groups. Ninety-eight participants consisting of 48 patients with CKD and 50 healthy individuals (age and gender matched) were included. Whole saliva and blood samples were collected and analyzed for concentrations of electrolytes (K+, Na+, Ca2+, Cl-, and HCO32-), total protein and IgA. Data were analyzed using Independent-Samples t-test and Pearson correlation test. Concentrations of salivary K+, Ca2+, Cl-, and total protein were higher; while concentrations of salivary Na+, HCO32- were lower in patients with CKD compared with healthy individuals. There was no difference in the salivary IgA levels in patients with CKD compared with healthy individuals. Salivary calcium level showed linear correlation with the plasma calcium level while salivary chloride level showed negative correlation with plasma chloride level among patients with CKD. These findings indicate that saliva and plasma from patients with CKD are characterized by higher potassium, chloride, and lower sodium concentrations than their levels in healthy individuals; thus, suggesting a possible increased adrenal-cortical activity in patients with CKD.